Regulation of cGAS/STING signaling and corresponding immune escape strategies of viruses - Ge, Zhe; Ding, Shuzhe (Frontiers in Cellular and Infection Microbiology, 2022)
Innate immunity is the first line of defense against invading external pathogens, and pattern recognition receptors (PRRs) are the key receptors that mediate the innate immune response. Nowadays, there are various PRRs in cells that can activate the innate immune response by recognizing pathogen-related molecular patterns (PAMPs). The DNA sensor cGAS, which belongs to the PRRs, plays a crucial role in innate immunity. cGAS detects both foreign and host DNA and generates a second-messenger cGAMP to mediate stimulator of interferon gene (STING)-dependent antiviral responses, thereby exerting an antiviral immune response. However, the process of cGAS/STING signaling is regulated by a wide range of factors. Multiple studies have shown that viruses directly target signal transduction proteins in the cGAS/STING signaling through viral surface proteins to impede innate immunity. It is noteworthy that the virus utilizes these cGAS/STING signaling regulators to evade immune surveillance. Thus, this paper mainly summarized the regulatory mechanism of the cGAS/STING signaling pathway and the immune escape mechanism of the corresponding virus, intending to provide targeted immunotherapy ideas for dealing with specific viral infections in the future.